Comprehensive performance improvement of standing wave thermoacoustic engine with converging stack: Thermodynamic analysis and optimization. (September 2019) - Liu, Liu; Yang, Peng; Liu, Yingwen
Highlights: Standing wave thermoacoustic engines with converging stack are investigated. yc / δkc is an important factor to optimize the stack and the performance. Acoustic power loss of the cold HX is analyzed. Converging stack can obtain higher efficiency and reduce the consumptive materials. Abstract: In a thermoacoustic engine, the ratio of the plate spacing to the thermal penetration depth crucial to the performance and efficiency of thermoacoustic conversion. However, the temperature gradient in the regenerator or stack causes the non-uniform distribution of the thermal penetration depth. In this paper, the thermoacoustic stack comprised of converging channels has been put forward and applied in a standing wave thermoacoustic engine. The influence of the ratio of the plate spacing to the thermal penetration depth at the cold end of the stack, yc / δkc, on the performance parameters of different models is investigated in detail. Results show that suitable value of yc / δkc in parallel and converging stack models can improve the acoustic power and efficiency. It is also found that the converging stack can basically replace the parallel stack with the same yc / δkc and reduce the cost of consumptive materials. A dimensionless parameter β is defined to evaluate the comprehensive performance of thermoacoustic engine and used to guide the design of the stack.